Willgerodt-Type Dichloro(aryl)-λ3-Iodanes: A Structural Study - Sarie, Jérôme C.; Neufeld, Jessica; Daniliuc, Constantin G.; Gilmour, Ryan (Synthesis, 2019)
Crystallographic structural analysis of four electronically diverse Willgerodt-type reagents is disclosed together with a solution-phase NMR analysis. These data reveal a plethora of intermolecular non-covalent interactions and confirm the expected T-shape geometry of the reagents. In all cases the I–Cl bonds are orthogonal to the plane of the aryl ring. This study provides important structural insights into this venerable class of dichlorination reagent and has implications for crystal engineering.
Keywords: chlorination; hypervalency; iodine(III); X-ray crystallography